The impact of eSports and online video gaming on lifestyle behaviours in youth: A systematic review. (January 2022) - Chan, Gary; Huo, Yan; Kelly, Sarah; Leung, Janni; Tisdale, Calvert; Gullo, Matthew
Abstract: Background: ESports has evolved into a hyper-competitive genre of video gaming. Emerging evidence has linked its intense engagement with mental health problems, with implications on youth development. We aim to summarise the impact of eSports and online video gaming on lifestyle outcomes. Method: We conducted a systematic review and meta-analysis of studies in journals published in the English language since 2011. We searched PubMed, Web of Science (WoS) and Bielefeld Academic Search Engine (BASE) using search strings related to eSports or video-gaming and lifestyle behaviours. Results: We identified 3694 studies, 36 of which met the inclusion criteria. The studies reported associations between online video gaming (including eSports participation and consumption) and poor lifestyle outcomes:physical activity-related (decreased levels of physical activity, increased body mass index (BMI) and sedentary behaviour)nutrition-related (poorer diet, sweetened beverage consumption) and sleep-related outcomes (decreased quality/duration, increased sleepiness/sleep deprivation). One study investigated physical lifestyle-related outcomes (eye strain, wrist pain, neck pain) Results indicate a widening breadth of research investigating associations between lifestyle outcomes and online video gaming. Conclusion: Lifestyle outcomes associated with engagement in eSports and video gaming are important to consider. This emphasizes the need for longitudinal studies which examine characteristics of gaming that may increase young people's risk of practicing unhealthy lifestyle behaviours. The accessibility of eSports to a wide digital audience highlights the need for this sector to promote healthy lifestyle behaviours among consumers and gamers. Highlights: We reviewed the impact of eSports and online video games on lifestyle behaviors among youth. Higher engagement with gaming was associated with poorer diet and lifestyle behaviors. Impacted outcomes related to physical activity, nutrition, physical lifestyle and sleep quality. There is a need for longitudinal studies examining gaming features associated with lifestyle. The popularity of online video gaming has potential to promote healthy lifestyle among youth.